2016
DOI: 10.1186/s12906-016-1460-y
|View full text |Cite
|
Sign up to set email alerts
|

Citrus junos Tanaka peel ameliorates hepatic lipid accumulation in HepG2 cells and in mice fed a high-cholesterol diet

Abstract: Background Citrus junos Tanaka (yuja), a yellow-coloured citrus fruit has traditionally been consumed in Korea, Japan, and China and has been found effective in preventing certain diseases. However, the inhibitory effect of yuja on hepatic lipid accumulation has not been clearly elucidated thus far.MethodsThe inhibitory effect of yuja on hepatic lipid accumulation was investigated in both cell culture and mouse models. We investigated the inhibitory effect of ethanol extract of yuja peel (YE) using HepG2 cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 18 publications
0
13
0
Order By: Relevance
“…The cellular study was carried out on HepG2 cells because the hepatocyte is the major cell involved in the clearance of plasma LDL cholesterol expressing the most numbers of active LDLR on its surface [ 16 ]. In addition, since HepG2 expresses differentiated hepatic functions, these cells are worldwide recognized as a good model for assessing the hypocholesterolemic effects of bioactive compounds from different sources [ 17 , 18 , 19 , 20 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…The cellular study was carried out on HepG2 cells because the hepatocyte is the major cell involved in the clearance of plasma LDL cholesterol expressing the most numbers of active LDLR on its surface [ 16 ]. In addition, since HepG2 expresses differentiated hepatic functions, these cells are worldwide recognized as a good model for assessing the hypocholesterolemic effects of bioactive compounds from different sources [ 17 , 18 , 19 , 20 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nakajima et al have reported that Citrus junos peel can attenuate dextran sulfate sodium-induced murine experimental colitis and that its anti-inflammatory effect is related to its bioactive components such as hesperidin and naringin [ 7 ]. Shin et al have found that 70% ethanolic extract of C. junos peel can reduce oleic acid-induced hepatic lipid accumulation in HepG2 cells with hypocholesterolemic effect in high-cholesterol diet mice models [ 8 ]. However, Shin et al did not give reasons for or show active markers about why 70% ethanol extract was used in their experiment.…”
Section: Introductionmentioning
confidence: 99%
“…As far as biological activity is concerned, yuzu is certainly the most investigated among the selected Citrus species. The fruit has been examined for its antiaging (Adhikari et al., 2017; Shim et al., 2019), neuroprotective (Yang et al., 2013), lipid‐ and cholesterol‐lowering (Kim et al., 2013; Sharma et al., 2019; Shin et al., 2016), anti‐inflammatory (Abe et al., 2018), and osteogenic activities (Jeon et al., 2016) both as a plant complex and as a source of promising isolated bioactive compounds. Moreover, it is the only fruit that has been clinically investigated, whereas the other ones have been studied mostly by in vitro cell‐free and cell‐based assays.…”
Section: Discussionmentioning
confidence: 99%
“…The AD-Y group showed a normal glucose tolerance, insulin sensitivity, and secretion, suggesting a yuzu preventive role on cognitive dysfunction, impaired energy, and glucose homeostasis induced by β-amyloid infusion (Yang et al, 2013). Shin, Park, Sung, Chung, and Hwang (2016) recently investigated the potential role of yuzu peel 70% ethanol extract (YE) on hepatic lipid accumulation on an in vitro cell-based model (HepG2 cells), as well as on a mouse model (Table 3).…”
Section: Citrus Junos Sieb Ex Tanmentioning
confidence: 99%
See 1 more Smart Citation